2013
DOI: 10.1029/2012gc004440
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Curie temperature

Abstract: [1] Curie point temperatures (T C ) of natural and synthetic magnetic materials are commonly determined in rock magnetism by several measurement methods that can be mutually incompatible and may lead to inconsistent results. Here the common evaluation routines for high-temperature magnetization and magnetic initial susceptibility curves are analyzed and revised based on Landau's theory of second-order phase transitions. It is confirmed that in high-field magnetization curves T C corresponds to the inflection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 25 publications
5
75
0
3
Order By: Relevance
“…The stepwise experiments NATURE COMMUNICATIONS | DOI: 10.1038/ncomms2938 ARTICLE involved a set of heating/cooling cycles with increases in T max for each cycle, usually in increments of 50 or 100°C. Curie temperatures were calculated from both the warming and cooling curves by finding inflection points of the w(T) or M S (T) curves, where the downward curvature of the ferrimagnetic state gives way to the upward curvature of the paramagnetic state 55,56 . In practice this was done by finding the temperature for which the first derivative of the (threepoint moving average) curve has a minimum (that is, greatest negative) value.…”
Section: Methodsmentioning
confidence: 99%
“…The stepwise experiments NATURE COMMUNICATIONS | DOI: 10.1038/ncomms2938 ARTICLE involved a set of heating/cooling cycles with increases in T max for each cycle, usually in increments of 50 or 100°C. Curie temperatures were calculated from both the warming and cooling curves by finding inflection points of the w(T) or M S (T) curves, where the downward curvature of the ferrimagnetic state gives way to the upward curvature of the paramagnetic state 55,56 . In practice this was done by finding the temperature for which the first derivative of the (threepoint moving average) curve has a minimum (that is, greatest negative) value.…”
Section: Methodsmentioning
confidence: 99%
“…Robust knowledge of this transformation temperature where all ferromagnetism ceases within a material is essential for the study, processing, and application of ferromagnetic compounds. Modern measurement of the Curie temperature is typically accomplished using some form of magnetometer measuring current induced by the magnetic field emanating from a material or zeroing out the material field with a compensating coil [6,7]. The earliest magnetization measurements and Curie temperatures were recorded using a special torsion balance that used the force of gravity to measure the magnitude of the magnetic field coming from a material via an effective mass change on the balance equilibrium position [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cooling curve is indicative for the occurrence of mineralogical changes caused by laboratory heating. Considerable effort has been put on theoretical and experimental studies, defining physical basis of the observed susceptibility changes (Egli, 2009;Fabian et al, 2013;Dunlop, 2014) and methodologies for estimation of the Curie temperature (Gromme et al, 1969;Petrovsky and Kapicka, 2006). The shape and the observed peaks on the heating and cooling curves of k-T cycles are interpreted as a reflection of different environmental processes [e.g., degree of soil formation and synthesis of pedogenic strongly magnetic fraction; presence of substitutions; reactions of Fe minerals with organic matter; destruction of thermally unstable minerals such as carbonates, organic matter, clay minerals (Liu et al, 2005;Hanesch et al, 2006;Jiang et al, 2015)].…”
Section: Introductionmentioning
confidence: 99%